A Maluku Sea intermediate western boundary current connecting Pacific Ocean circulation to the Indonesian Throughflow - Dongliang Yuan; Xueli Yin; Xiang Li; Corry Corvianawatie; Zheng Wang; Yao Li; Ya Yang; Xiaoyue Hu; Jing Wang; Shuwen Tan; Dewi Surinati; Adi Purwandana; et al. (Nature Communications, 2022)
Here the authors use in situ mooring data in the Maluku Channel and the Lifamatola Passage of the Indonesian seas to show that a western boundary current transports Antarctic water from the South Pacific to the Indian Ocean.